Can vitamin supplements improve sport performance? - Benardot, D.; Coleman, E.; Clarkson, P.; Manore, M. (2001)
Vitamin deficiencies among various groups of athletes are uncommon, but there are some individual athletes within groups who are vitamin deficient. The most common deficiencies are for the B-complex vitamins (especially B-6 and folate), and for the antioxidant vitamins C, E, and beta-carotene. Athletes most likely to suffer vitamin deficiencies include wrestlers, dancers, gymnasts, and others who restrict their food intake to maintain a low body weight, athletes who have too little time to select and/or eat well-balanced diets, athletes whose diets are too rich in fast food items, and athletes who eat few fruits and vegetables. Vitamin overload in athletes is unlikely unless they are consuming large doses of vitamin supplements and/or large amounts of vitamin-fortified foods. Athletes who wish to be on the "safe side" of avoiding vitamin deficiencies may wish to take a multi-vitamin/multi-mineral supplement each day or every other day. The supplement should not exceed the Recommended Dietary Allowance or Adequate Intake for the vitamin(s). Vitamin supplements can improve sport performance only in athletes who are vitamin deficient. Athletes who have normal stores of vitamins will not benefit from consuming vitamin supplements. Vitamins obtained from natural foods are preferred over vitamin supplements because the natural foods contain important nutrients that can be deficient if athletes rely on supplements.